2012
DOI: 10.1111/j.1469-5812.2010.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Critical Thinking Skills among College Graduates: Implications for leadership

Abstract: Although higher education understands the need to develop critical thinkers, it has not lived up to the task consistently. Students are graduating deficient in these skills, unprepared to think critically once in the workforce. Limited development of cognitive processing skills leads to less effective leaders. Various definitions of critical thinking are examined to develop a general construct to guide the discussion as critical thinking is linked to constructivism, leadership, and education. Most pedagogy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 68 publications
(105 reference statements)
1
90
0
3
Order By: Relevance
“…Transfer is influenced by factors such as: the generalisability of the intended learning (principles and concepts versus facts); the sophistication of learner self-monitoring and self-explanations; the role of others; the nature and extent of feedback; and the extent to which self-regulation is required (Billing, 2007). As well as there being no common understanding of optimum balance between content and cognitive processing (Prøitz, 2010), cognitive processing implicates an array of intellectual skills, the full range of which may not be in pedagogical focus (Flores, Matkin, Burbach, Quinn, & Harding, 2010).…”
Section: Teaching As Triggering Cognitionmentioning
confidence: 99%
“…Transfer is influenced by factors such as: the generalisability of the intended learning (principles and concepts versus facts); the sophistication of learner self-monitoring and self-explanations; the role of others; the nature and extent of feedback; and the extent to which self-regulation is required (Billing, 2007). As well as there being no common understanding of optimum balance between content and cognitive processing (Prøitz, 2010), cognitive processing implicates an array of intellectual skills, the full range of which may not be in pedagogical focus (Flores, Matkin, Burbach, Quinn, & Harding, 2010).…”
Section: Teaching As Triggering Cognitionmentioning
confidence: 99%
“…In contrast to this common epistemic element is the claim that there is no unanimous definition of critical thinking (Flores, Matkin, Burbach, Quinn & Harding, 2012). Nevertheless, three common dimensions for critical thinking have been suggested, namely the ability to perform rational and reasonable thinking, the ability to see alternative viewpoints, and the ability to reflect on one's own thinking and its quality (Niu et al, 2013;Flores et al, 2012).Like the definitions of critical thinking, the research results on learning critical thinking skills as an outcome of university studies are also conflicting. In some studies, participation in higher education has been found to develop certain elements of students' critical thinking, that is, the ability to approach problems from various viewpoints (Kim, Sharma, Land & Furlong, 2013), and to evaluate knowledge and make informed judgments (Wass, Harland & Mercer, 2011).…”
mentioning
confidence: 99%
“…Ennis (2008) has labeled views of this kind as epistemic approaches to the conception of critical thinking, since they share the purpose of finding the truth or at least the closest approximation to it. In contrast to this common epistemic element is the claim that there is no unanimous definition of critical thinking (Flores, Matkin, Burbach, Quinn & Harding, 2012). Nevertheless, three common dimensions for critical thinking have been suggested, namely the ability to perform rational and reasonable thinking, the ability to see alternative viewpoints, and the ability to reflect on one's own thinking and its quality (Niu et al, 2013;Flores et al, 2012).…”
mentioning
confidence: 99%
“…Similarly, Flores, Matkin, Burbach, Quinn, and Harding (2012) support the shifting of education from teaching content to teaching students how to become critical thinkers. Today, it should be the concern of every teacher to develop the critical thinking skill of every student.…”
Section: Introductionmentioning
confidence: 99%